The Role of Social Media Campaigns in Enhancing Corporate Sustainability Initiatives: A Study of Selected Companies in Southeast Asia - Syahirah Gunawan; Rino Febrianno Boer (Ilomata International Journal of Social Science, 2026)
Social, environmental and economic pressures are increasing the urgency of corporate sustainability in Southeast Asia, while encouraging companies to use social media as a campaign channel and strategic communication tool. This study, grounded in the Triple Bottom Line (TBL) framework, Stakeholder Theory, and Corporate Communication Theory, explores how selected Southeast Asian companies utilize social media to enhance sustainability initiatives which also serve as a bridge between the perspectives of business ethics, marketing communications, and sustainable development. Through a qualitative, secondary data approach, the research examines specific case studies including Pertamina, Petronas, and Thai Union Group, to assess strategies, challenges, and engagement effectiveness. The data analysed consists of relevant previous research and documentation from the companies concerned. This study does not directly measure the effectiveness of engagement, but rather interprets the effectiveness of engagement in terms of narrative coherence. The study also addresses recent criticisms of the TBL framework, highlighting ethical tensions between profitability and moral responsibility. Findings reveal that localized storytelling, influencer collaboration, and transparency tend to enhance stakeholder trust and campaign resonance. However, inconsistencies in messaging and the risk of performative activism remain critical issues. By integrating empirical cases and theoretical critique, this research contributes to a more nuanced understanding of how digital platforms mediate corporate sustainability in diverse Southeast Asian contexts. The study concludes with recommendations for more stakeholder driven and ethically coherent communication strategies.